Perbandingan ralat ‘multipath’ bagi data cerapan GPS stesen MASS dan stesen RTK - Mardina Abdullah,; Norbahiah Misran,; Nor Nadira M. Ariff,; M. Fazrin Abdullah, (2010)
Multipath is one of the major sources of error in GPS code and carrier phase measurements that prevents the achievement of the highest levels of accuracy in GPS applications. Multipath occurs when signals travelling from a transmitter to a receiver propagate via multiple paths due to reflection and diffraction. The aim of this paper is to analyze the effect of multipath between MASS (Malaysia Active GPS System) station and GPS RTK (GPS Real Time Kinematic) reference station. The data is analysed from 15 MASS stations and 27 GPS RTK reference stations that are strategically located throughout Malaysia. This research also identifies which station between MASS station and GPS RTK reference stations are the most and least affected by multipath effect of both pseudo ranges at L1 (1575.42 MHz) and L2 (1227.60 MHz) of GPS signals. TEQC (Translating, Editing and Quality Checking) software is used to obtain multipath errors for both GPS signals. Based on the results, it is shown that the multipath error effects highly affect pseudo ranges for carrier frequency L2 more than the carrier frequency L1 which is consistent with previous research findings. It is shown that the most affected GPS data for multipath at L1 is from GPS RTK reference station and the least is from MASS station. The most affected at L2 is from MASS station and the least from GPS RTK reference station. For further research, more data are needed to be analyzed and better methods are required to analyze GPS data